THE EFFECT OF INTELLECTUAL CAPITAL ON FIRM VALUE WITH CORPORATE GOVERNANCE AS A MODERATING VARIABLE - Darmiani; Muliati; Ansar, Muhammad (APSSAI, 2024)
This study examines and analyzes the effect of firm size, enterprise risk management, and intellectual capital on firm value with good corporate governance as a moderating variable using sample mining sector companies listed on the Indonesia Stock Exchange for 2017-2021. The data analysis method used is Partial Least Square with WarpPLS 7.0 software. The results indicate that a significant and positive partial effect of firm size has a significant positive effect on firm value. Still, enterprise risk management and intellectual capital have indicated a significant and negative partial effect on firm value. Regarding the moderation effect, most findings show that GCG does not moderate the relationship between enterprise risk management and intellectual capital on firm value.